MENTAL PREPARATION OF THE POPULATION TO ACT CORRECTLY IN EMERGENCY SITUATIONS - Abdurakhmonova Sayorakhan Ruzalievna (Galaxy International Interdisciplinary Research Journal, 2023)
Mental preparation in civil protection is the education of the belief that the performance of civil protection duties is a duty to the country and the people, it is the understanding of the need to conscientiously perform one’s duties in times of peace and military operations, to overcome difficulties in such situations, and education in the spirit of endurance to mental difficulties.